Constructing Community and Nation in the Archipelago: Yesterday, Today and Tomorrow - Glinton-Meicholas, Patricia (International Journal of Bahamian Studies, 2013)
Plenary address at the College of The Bahamas Independence conference, The Bahamas at 40: Reflecting on the Past, Envisioning the Future.